MOGAD in the Mountain West: Epidemiology and Outcomes in Pediatric and Adult Patients at Two Large Academic Referral Centers. (5th December 2022) - Wright, Melissa; Liu, Suzanne; Wong, Ka-Ho; Mizenko, Christopher; Kammeyer, Ryan; Schreiner, Teri; Kadish, Robert; Smith, Tammy; Galli, Jonathan; Klein, Julia; Greenlee, John; Rose, John; et al.
Abstract : Objective: To describe the characteristics and outcomes in adult and pediatric patients diagnosed with myelin oligodendrocyte glycoprotein antibody-associated disease (MOGAD) at the two major referral centers in the Mountain West of the United States, a geographic area encompassing roughly 15% of the land mass of the continental US. Background: Since the development of commercial assays, MOGAD has become increasingly recognized as an etiologic diagnosis for several CNS demyelinating phenotypes, yet the epidemiological characteristics, relapse rates and outcomes of large populations are not well-described Design/Methods: A retrospective chart review for patients within the health systems at the University of Utah and the University of Colorado, and affiliated children's hospitals, was conducted. To identify MOGAD patients, we queried the ICD10 codes corresponding to demyelinating disease of CNS, neuromyelitis optic spectrum disease, optic neuritis, transverse myelitis, and acute disseminated encephalomyelitis. These patients were then cross matched against antibody testing results and existing research databases at each institution. Search dates included 1/1/2016-12/1/2021 to encompass the period of commercially available MOG IgG testing. Patients were cross referenced with a list of positive MOG IgG assays at each institution. Results: We describe the characteristics of over 50 patients (adults and children) with MOGAD, including age of onset, gender, symptoms at onset, associated autoimmunity, antibody titers, response to therapies and relapse rates. Conclusions: This is a comprehensive characterization of a diverse population of pediatric and adult MOGAD patients seen at the two major referral hospitals in the Mountain West. The treatment regimens and outcomes in this population may inform approaches to current management and future clinical trials.